2014
DOI: 10.1177/0954405414542855
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and optimization of equivalent plastic strain in equal-channel angular rolling using response surface methodology

Abstract: The mechanical properties of metallic strips can be improved by producing an ultra-fine-grained microstructure. The equal-channel angular rolling process is a severe plastic deformation technique suitable for such a purpose. In this article, the effect of the equal-channel angular rolling parameters on the equivalent plastic strain is investigated and their optimum values are reported. The analysis is focused on the following parameters: thickness ratio (K), die channel angle (u), die outer corner angle (c), f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…In this simulation, the strip is divided into 8900 nodes and 8001 elements. Therefore, in Chari et al, 24 the validation of the FEM simulation has been done and confirmed by comparing of the inclination angle with an analytical approach. Moreover, using some analytical equations, the obtained strain from the simulation was compared with the analytical relations.…”
Section: Finite Element Analysismentioning
confidence: 95%
See 1 more Smart Citation
“…In this simulation, the strip is divided into 8900 nodes and 8001 elements. Therefore, in Chari et al, 24 the validation of the FEM simulation has been done and confirmed by comparing of the inclination angle with an analytical approach. Moreover, using some analytical equations, the obtained strain from the simulation was compared with the analytical relations.…”
Section: Finite Element Analysismentioning
confidence: 95%
“…Results showed that shear deformation, stress homogeneity and strain distribution can be improved due to the friction between the die walls and the workpiece. Chari et al 24 utilized both the response surface methodology and the finite element method (FEM) to predict the effect of process parameters on equivalent plastic strain in ECAR. The results indicated that the friction coefficient on the interface of the rolls and strip has no significant effect on effective strain, while the die channel angle is the most considerable parameter.…”
Section: Introductionmentioning
confidence: 99%
“…To assess the friction coefficient effect on the imposed strain (for lubrication condition) three values of 0.14, 0.17 and 0.21 has been considered [5,19]. These effects are shown in Figure 10.…”
Section: Effect Of Friction Coefficient On the Effective Strainmentioning
confidence: 99%
“…So far, a a Corresponding author: a asgari@mecheng.iust.ac.ir few researchers have been reported on the ECAR process. For example, Chari et al [5] presented modeling and optimization of equivalent plastic strain in equal-channel angular rolling using response surface approach. Chung et al [6] introduced an analysis of accumulated deformation in the equal channel angular rolling process.…”
Section: Introductionmentioning
confidence: 99%
“…So far, very few studies have been presented an assessment of significant parameters using statistical method on the SPD processes and particularly ECFE process. For example, Chari et al 16 presented modeling and optimization of equivalent strain in equal channel angular rolling (ECAR) using RSM. Mohammed Iqbal and Kumar 17 presented a study about application of RSM in twist extrusion process parameters of Al-6082.…”
Section: Introductionmentioning
confidence: 99%